PENGARUH HUMAN RELATION, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA LPD DESA PAKRAMAN PADANGSAMBIAN - I Ketut Endi Parta; Ni Wayan Eka Mitariani; I Gede Yudhi Hendrawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Performance is a result of the work achieved by a person in carrying out the tasks assigned to him based on skills, experience, and seriousness and time. There are several factors that can affect employee performance, including human relations, motivation, and organizational culture. This study aims to explain the effect of human relations, motivation, and organizational culture on employee performance at LPD Desa Pakraman Padangsambian. The population in this study were all employees of the LPD Desa Pakraman Padangsambian, totaling 35 people. The sampling technique used is saturated sampling technique, where the entire population is used as a sample of 35 people. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that human relations had a positive effect on employee performance, motivation had no effect on employee performance, and organizational culture had a positive effect on employee performance. Suggestions for further research can develop this research by adding other variables such as compensation and work environment.